The use of tree-rings and foliage as an archive of volcanogenic cation deposition. - Watt, S; Pyle, D; Mather, T; Day, J; Aiuppa, A (2007)
Tree cores (Pinus nigra ssp. laricio) and leaves (Castanea sativa) from the flanks of Mount Etna, Sicily were analysed by ICP-MS to investigate whether volcanogenic cations within plant material provide an archive of a volcano's temporal and spatial depositional influence. There is significant compositional variability both within and between trees, but no systematic dendrochemical correlation with periods of effusive, explosive or increased degassing activity. Dendrochemistry does not provide a record of persistent but fluctuating volcanic activity. Foliar levels of bioaccumulated cations correspond to modelled plume transport patterns, and map short-term volcanic fumigation. Around the flanks of the volcano foliar variation is greater for volatile cations (Cs, Cd, Pb) than for lithophilic cations (Ba, Sr), consistent with trace-metal supply from volcanic aerosol during quiescent periods.